QTLs for phosphorus deficiency tolerance detected in upland NERICA varieties. Issue 3 (19th April 2013) - Koide, Yohei; Pariasca Tanaka, Juan; Rose, Terry; Fukuo, Ayumi; Konisho, Kunihiko; Yanagihara, Seiji; Fukuta, Yoshimichi; Wissuwa, Matthias; Yano, M.
Abstract Phosphorous (P) deficiency is a major yield limiting factor in rice (Oryza sativa L.) production. The interspecific New Rice for Africa (NERICA) varieties combine general stress tolerance from African cultivated rice (Oryza glaberrima Steud) with characteristics associated with high yield from O. sativa. However, little is known about their ability to tolerate P deficiency. Here, we examined the variation for tolerance to P deficiency among the 18 upland NERICAs and their parents in multi‐year field experiments. The good performance under P deficiency of the O. glaberrima parent CG 14 and some NERICAs suggested that these tolerant NERICAs contain loci associated with P deficiency tolerance inherited from CG 14. Additionally, four QTL clusters for P deficiency tolerance were detected on chromosomes 4, 6 and 11 using F3 lines derived from the cross between the P deficiency tolerant variety NERICA10 and a Japonica‐type sensitive variety 'Hitomebore'. These QTLs represent the first step in identifying stress tolerance genes from O. glaberrima that could subsequently be used to enhance P deficiency tolerance in O. sativa.